FIGURATIVE LANGUAGE IN THE SONG LYRIC OF TAYLOR SWIFT’S ALBUM “RED” - Jufri, Muhammad Dzulkhair; Weda, Sukardi (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
The purpose of this study is to identify the kinds of metaphorical language and its significance in the Red album. The researchers employ Perrine's theory of figurative language to assess the data. The researchers employed a qualitative study design. This study also employed a semantic approach to ascertain the relationships between words, phrases, and sentences. According to the research, the Red Album uses nine different figurative language types, including simile, metaphor, personification, metonymy, synecdoche, hyperbole, irony, and symbolism. The information was taken from song lyrics. Some examples include the songs Red, Treacherous, I Knew You Were Trouble, All Too Well, 22, I almost do, We Are Never Getting Back Together, Stay Stay Stay, The Last Time, Holy Ground, Sad Beautiful Tragic, The Lucky One, Everything Has Changed, Starlight, Begin Again, and Come Back... Be Here and with other people. The study found about 32 samples of figurative language. The researchers also learned the significance of Red. 32 meaning extracts were uncovered by the researchers.